Psychometric Properties of the Academic Self Concept Scale among Indian CBSE School Students - R. Gayatri Iyengar; G. Padma Gouri; Mahendra Kumar (Medsci Publications, 2021)
Introduction: Psychometrically sound instruments are required to reliably measure academy self concept for school students. For this study, we validate the academy self concept scale (ASCS) with students 16+ years. The objective of this study is to examine the factor structure, validity, and reliability of the 57-item academic self- concept scale in a Indian School Students. Methods: The participants of the study are constituted by 581 students studying in CBSE Private School in 2021-2022 education year. All of the participants were subjected to the academic self- concept scale. Confirmatory factor analysis methods were used to examine the structural validity of academic self- concept scale. The reliability of academic self- concept scale was examined with, internal consistency. Results: Confirmatory factor analysis in the sample confirmed an 8-factor model with indices of fitness that indicated a satisfactory model fit (goodness of fit index = 0.99; Tucker-Lewis index = 0.89; comparative fit index = 0.92; root mean square error of approximation = 0.1173; Standardized root mean square residual=0.0445). Our analyses support a eight-factor model of responses to the ASCS (Academic Ability, Academic Interest, Study, Examination, Academic Interactions, Academic efforts, Curriculum and Academic future) measuring a higher order latent construct. It was seen that the factor loads of the scale varied between 0.5952 and 0.8690. The internal consistency of the scale was 0.918. Conclusion: The findings obtained in this study indicate that the academic self- concept scale has a eight-factor structure and this form can be used as a valid and reliable measuring means in evaluating academic self- concept in CBSE school students.